2016
DOI: 10.7554/elife.17985
|View full text |Cite
|
Sign up to set email alerts
|

Pask integrates hormonal signaling with histone modification via Wdr5 phosphorylation to drive myogenesis

Abstract: PAS domain containing protein kinase (Pask) is an evolutionarily conserved protein kinase implicated in energy homeostasis and metabolic regulation across eukaryotic species. We now describe an unexpected role of Pask in promoting the differentiation of myogenic progenitor cells, embryonic stem cells and adipogenic progenitor cells. This function of Pask is dependent upon its ability to phosphorylate Wdr5, a member of several protein complexes including those that catalyze histone H3 Lysine 4 trimethylation (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(67 citation statements)
references
References 73 publications
6
61
0
Order By: Relevance
“…Nutrients and Insulin Activate PASK in an mTORC1-Dependent Manner. We have previously reported that PASK expression was induced several-fold upon skeletal muscle injury and that loss of PASK resulted in severe defects in muscle regeneration (21). We showed that PASK activity was also posttranslationally stimulated during in vitro myogenesis (21).…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Nutrients and Insulin Activate PASK in an mTORC1-Dependent Manner. We have previously reported that PASK expression was induced several-fold upon skeletal muscle injury and that loss of PASK resulted in severe defects in muscle regeneration (21). We showed that PASK activity was also posttranslationally stimulated during in vitro myogenesis (21).…”
Section: Resultsmentioning
confidence: 77%
“…We have previously reported that PASK expression was induced several-fold upon skeletal muscle injury and that loss of PASK resulted in severe defects in muscle regeneration (21). We showed that PASK activity was also posttranslationally stimulated during in vitro myogenesis (21). To understand if this activation of PASK is required for its prodifferentiation functions, we first asked if PASK is similarly activated during muscle regeneration in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations